Perlindungan Hukum Hak-hak Anak di Panti Asuhan Pelangi Palembang - Hidayah, Ardiana; Adisti, Neisa Angrum; Banjarani, Desia Rakhma; Aprita, Serlika; Nurlani, Meirina (CV. Doki Course and Training, 2025)
Children, as a trust and a gift from God Almighty, possess inherent rights, dignity, and worth as complete human beings. Within the context of national law, the state is obligated to provide protection for children’s rights as stipulated in Law Number 35 of 2014 on Child Protection, which amends Law Number 23 of 2002. Such protection includes the right to life, growth and development, education, protection from violence, and the right to social welfare. Children living in orphanages constitute a vulnerable group requiring special attention, both in terms of the fulfillment of basic needs and legal protection. This community service activity was conducted at Pelangi Orphanage in Palembang with the aim of enhancing the understanding of orphanage administrators and foster children regarding the legal protection of children’s rights, as well as encouraging the creation of a child-friendly and legally oriented orphanage environment. The method employed was a participatory-educational approach through interactive legal counseling, discussions and question-and-answer sessions, as well as simple case studies tailored to the conditions of the children and the orphanage management. The results indicate an improvement in participants’ legal understanding of children’s rights and the obligations of orphanage administrators, increased awareness among foster children regarding their right to protection from violence and discrimination, and the establishment of a commitment by the administrators to create a safe, comfortable, and child-friendly environment in accordance with the principles of child protection. This activity has a positive impact in the form of increased legal awareness and capacity within the orphanage environment, which is expected to be sustainable in supporting children’s welfare and protection.